Measurement of Organizational Climate of the Coohilados cooperative at the municipality of SanGil - Díaz Uribe, Carlos Alonso; Gomez Mutis, Sergio Andres (Universidad Francisco de Paula Santander, 2017)
Organisational climate is the sensation, personality or character of the environment of an organization,something that distinguis he sone company from another,being theset of characteristics of an organization that affects the work environment and influences the behavior of people.(Sánchez,2006,p.42).The investigation began by collecting necessary information provided by the instruction and measurement of working environment of the employees with in the organisation ‘ COOHILADOS Cooperativa of FONCE’ from the beginningof the year until mid-2017. It involved analysis of the Organizational Climate to identify the areas that represent strengths and opportunities (WeakPoints orCritical Points) in order to facilitate the decision making of top management and at the same time will allow the company to be successful and main tain it self as a competitive cooperative in respective sector. Result contributes to the socio-cultural advancement of the region.